Jinn and mental Illness among Muslims -a commentary - Md Rosli, Ahmad Nabil; Hashi, Abdurezak Abdulahi; Razali, Zul Azlin (2020)
It is common for Muslims to associate mental illness with the work of jinn. Typically, an initial consultation with folk-healer is made within the local community by those who experience deviant symptoms. This behaviour results in several serious negative health implications. Misconception about the meaning of Islamic medicine, the use of ruqyah among the public, and the lack of culturally competent approach in handling mental illnesses are thought to perpetuate the problem. Despite the lack of evidence in the Qur'an and Sunnah to support jinn possession, the belief persists in the community. Thus, a multidisciplinary approach through engagement, advocacy, and research are much needed to manage the issue at hand